KONSEP WUDHU DALAM PERSPEKTIF EMPAT MAZHAB: HANAFI, MALIKI, SYAFI’I DAN HAMBALI - Ulfatussyarifah; Nafidatun Nisa; Ahmad Zidni Khoiril Hakim; Lutfiyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The issue of ablution remains an interesting topic of debate among Muslims, particularly in relation to the differing views of the four major madhhabs of Hanafi, Maliki, Shafi'i and Hambali. Although the basic principle of wudhu, which is to cleanse the body with water in order to perform acts of worship such as prayer, is similar in all madhhabs, there are variations in technical matters related to certain procedures and requirements. There are different views regarding wiping the head during wudhu, the opinions of the four madhhabs stem from various factors, including differences in understanding the main arguments regarding the obligation to wipe the head found in Qs Al-Maidah verse 6 and fiqh books. This study aims to analyze the fardhu wudhu, sunnah wudhu, things that invalidate wudhu and views on wiping the head in the perspective of the four madhhabs namely Hanafi, Maliki, Shafi'i and Hambali. The main focus of the research is to understand the application of the concept of wudhu in the differences between the four madhhabs. The methods used include literature study and qualitative analysis of the sources. The findings show that the views of the four madhhabs on the concept of ablution are different but still have the same purpose. The benefit of this research is that it provides new insights into the views of the people in following one of the madhhabs regarding ablution despite differences in understanding.